Tunable Bandgap Design of Soft Phononic Crystals Using Topology Optimization (Adv. Theory Simul. 7/2022). Issue 7 (12th July 2022) - Luo, Yangjun; Li, Yan
Abstract : Tunable Bandgap Design of Soft Phononic Crystals Using Topology Optimization Tunable band gap designs of mechanism‐driven soft PnCs composed of hyperelastic materials is reported in article number 2100620 by Yangjun Luo and Yan Li. The gradient‐free MFSE topology optimization method provides an effective way to design soft PnCs with the maintenance, opening and closing of arbitrary order bang gaps using tensile deformation.